A Pregnant Lady with Thyrotoxic Cardiomyopathy and Pulmonary Hypertension (KYAMC Journal, 2020)
Thyrotoxic cardiomyopathy is potentially life threatening complications of thyrotoxicosis during pregnancy due to its harmful effects both on mother and fetus. We present a case of 32-year-old pregnant lady presented with non-productive cough, palpitation, restlessness, sweating and weakness after minimum exertion with a small swelling on the right side of her neck for three months. There was tachycardia with normal blood pressure, first and second heart sound were soft with pansystolic murmur on mitral and tricuspid area. After all laboratory investigations, she was diagnosed as dilated cardiomyopathy with moderate to severe pulmonary hypertension with toxic multi nodular goiter with 13 weeks of pregnancy.The thyrotoxic cardiomyopathy during pregnancy is rare due to difficulties in diagnosis. However, physicians should be aware of the risk posed by thyrotoxic cardiomyopathy during pregnancy.KYAMC Journal Vol. 11, No.-1, April 2020, Page 54-56